2018
DOI: 10.3390/universe4070080
|View full text |Cite
|
Sign up to set email alerts
|

A Scale at 10 MeV, Gravitational Topological Vacuum, and Large Extra Dimensions

Abstract: Abstract:We discuss a possible scale of gravitational origin at around 10 MeV, or 10 −12 cm, which arises in the MacDowell-Mansouri formalism of gravity due to the topological Gauss-Bonnet term in the action, as pointed out by Bjorken several years ago. A length scale of the same size emerges also in the Kodama solution in gravity, which is known to be closely related to the MacDowell-Mansouri formulation. We particularly draw attention to the intriguing incident that the existence of six compact extra dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 112 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…By comparison, a similar mass value has been argued [53] to be natural by examining a dimension-6 analogue of Weinberg's operator, where a neutrino could acquires its mass from a fermionic condensate controlled by the Bjorken-Zeldovich scale, with the electroweak cutoff scale:…”
Section: Neutrinosmentioning
confidence: 82%
See 1 more Smart Citation
“…By comparison, a similar mass value has been argued [53] to be natural by examining a dimension-6 analogue of Weinberg's operator, where a neutrino could acquires its mass from a fermionic condensate controlled by the Bjorken-Zeldovich scale, with the electroweak cutoff scale:…”
Section: Neutrinosmentioning
confidence: 82%
“…analogously to the relation (23), for the first of the Heisenberg algebras in (53). The holographic bound [11,12] for the effective spacetime associated with the vacuum energy is N Λ = l 2 Λ /l 2 P , which with (54) produces…”
Section: Cosmological Scalementioning
confidence: 88%
“…Given the difficulties of finding UV-finite quantum gravity and its small coupling constant, GUTs were proposed to unify all of the fundamental forces besides gravity. Recently, it has been suggested that torsion allows for UV-complete fermions [110][111][112], while the Gauss-Bonnet term allows for two-loop graviton scattering [113], both of which are related to the MacDowell-Mansouri formalism [114][115][116][117] studied in various graviGUT models [61,118]. Grand unified theory has been studied in a supersymmetry or supergravity context [6,18,21,24,29,36,45,47,48,52,54].…”
Section: Introductionmentioning
confidence: 99%
“…Given the difficulties of finding UV-finite quantum gravity and its small coupling constant, GUTs were proposed to unify all of the fundamental forces besides gravity. Recently, it has been suggested that torsion allows for UVcomplete fermions [110][111][112], while the Gauss-Bonnet term allows for two-loop graviton scattering [113], both of which are related to the MacDowell-Mansouri formalism [114][115][116][117] studied in various graviGUT models [61,118].…”
mentioning
confidence: 99%